VD_FINDINFO HC / 2018 / 574 vom 26. Juni 2018 - VD Tribunal cantonal (2018)
CONTRAT D'ENSEIGNEMENT, RÉSILIATION EN TEMPS INOPPORTUN, INDEMNITÉEN GÉNÉRAL, CLAUSE PÉNALE | 1 al. 1 CO, 163 CO, 3 CO, 404 al. 2 CO, 5 al. 1 CO, 6 CO